The Oxford Handbook of the Sociology of Body and Embodiment - Boero, Natalie; Mason, Katherine (Oxford University Press, 2019)
The Oxford Handbook of the Sociology of Body and Embodiment challenges the view that bodies belong to the category of "nature" and are biological, essential, and pre-social. It argues instead that bodies both shape and get shaped by human societies. As such, the body is an appropriate and necessary area of study for sociologists. The Handbook works to clarify the scope of this topic and display the innovations of research within the field. The volume is divided into three main parts: Bodies and Methodology; Marginalized Bodies; and Embodied Sociology. Sociologists contributing to the first two parts focus on the body and the ways it is given meaning, regulated, and subjected to legal and medical oversight in a variety of social contexts (particularly when the body in question violates norms for how a culture believes bodies "ought" to behave or appear). Sociologists contributing to the last part use the bodily as a lens through which to study social institutions and experiences. These social settings range from personal decisions about medical treatment to programs for teaching police recruits how to use physical force, from social movement tactics to countries' understandings of race and national identity. Many chapters throughout the book offer extended methodological reflections, providing guidance on how to conduct sociological research on the body and, at times, acknowledging the role the authors' own bodies play in developing their knowledge of the research subject.